Characterization of Mycosporine-Like Amino Acids in Chlorophyll f Producing Cyanobacteria from Shaded Niches - Maina Boukar, Mamadou Chetima; Saley, Moussa Diagara; Chetima Bagana, Mai Moussa; Wang, Kai; Zhang, Zhong-Chun; Qiu, Bao-Sheng; Ali, Mahamane (European Scientific Journal, ESJ, 2024)
Cyanobacteria are the oldest photoautotrophic prokaryotes that can perform plant-like oxygenic photosynthesis. The obligate requirement of sunlight for photosynthesis inevitably exposes cyanobacteria to UV radiation. Mycosporine-like amino acids (MAAs) played necessary roles in protecting cyanobacteria from UV radiation and were frequently reported in cyanobacteria exposed to high light radiation. Here, the MAA production was tried in the chlorophyll f-producing cyanobacterial strains isolated from the shaded environments. Four Chroococcidiopsis strains were finally induced to produce MAAs under 0.15 WÂ·m-2 of UV-B exposure, and the MAA contents increased along with the prolonged UV-B treatments in these four Chroococcidiopsis strains. After separation by HPLC system, one MAA type was detected at the similar retention times in the methanol extracts of Chroococcidiopsis strains, and all the MAA compounds showed in-line absorption at 310 nm and mass spectra 246 m/z. The absorption spectra and mass spectra matched well the characteristics of the simplest MAA mycosporine-glycine. Chroococcidiopsis had the simplest MAA gene clusters for mycosporine-glycine. MAAs could also be produced in the cyanobacteria even distributed in the light-deficient niches. These results suggested other roles of MAAs in addition to UV-B protection in the special cyanobacteria from shaded environments.